P1187Pocket-Hematoma after cardiac implantable electronic devices surgery: a single centre study. (18th June 2020) - Spighi, L; Notaristefano, F; Annunziata, R; D"ammando, M; Zingarini, G; Verdecchia, P; Cavallini, C
Abstract: Intro: Pocket hematoma is a common complication after pacemaker (PMK) or implantable cardioverter defibrillator (ICD) surgery. In this clinical setting anticoagulant and antiplatelet therapy are associated with an increased risk of hemorrhagic complications, but data are sparse. Purpose: We examined  the impact of antiplatelet therapy and anticoagulation with vitamin K antagonists (VKA) or heparin on the risk of pocket hematoma. Materials and method: between august 2017 and june 2019, a total of 639 devices were implanted or replaced at our centre. Predictors of hematoma occurrence were determined by multivariate regression analysis. We used a specific definition of pocket hematoma: a) any palpable swelling in the pocket area requiring an unscheduled visit or prolonged hospitalization > 24 h or re-hospitalization for hematoma, b) interruption of antithrombotics, c) reoperation, d) hemoglobin drop > 2 g/dl or blood transfusion. The above criteria were assessed during hospitalization and up to 10 days after discharge. Results: the incidence of pocket hematoma was 7.5%. Among 639 patients (pts) including in the study 33.5% (214 pts) didn' t take any antithrombotic therapy, 40.2 % (257 pts) were on single antiplatelet therapy (SAPT), 8.8 % (56 pts) were on dual antiplatelet therapy, 11.1 % (71 pts) were on uninterrupted VKA (mean INR 2). Heparin bridging was administered in 6.4% (41 pts). Ejection fraction (43 ±13 %) and  hemoglobin value before implantation (12.3 ±2.6 g/dL) in patients who developed hematoma were significantly lower compared with whose without hematoma. Patients with hematoma had a higher prevalence of congestive heart failure, ischemic cardiomyopathy and intake antithrombotic therapy. After adjusting for confounding factors with multivariate logistic regression only the use of dual antiplatelet therapy (OR 5.9 95% CI 1.5-21 p = 0.008) and the bridging with enoxaparin (OR 5.6 95% CI 1.4-22 p = 0.013) increased the risk of pocket hematoma. Single antiplatelet therapy (OR 2.6 95% CI 0.8-8.4 p = ns) and uninterrupted VKA (OR 0.9 95% CI 0.7-11 p = ns) did not increased the risk of pocket hematoma compared to no antithrombotic therapy. Pulse generator change and new device implant/upgrading (OR 1.8 95% CI 0.6-5.2 p = ns) carried the same haemorrhagic risk. Conclusion: the use of DAPT or bridging with enoxaparin are highly predictive for the occurrence of perioperative pocket hematoma in patients scheduled for pmk/icd surgery. In contrast, single antiplatelet therapy and uninterrupted VKA  did not increase the risk of hematoma.